Activity of Matrix Metalloproteinase-7 (MMP-7) Related to Heparin-Binding Epidermal Growth Factor (HB-EGF) Activation in Squamous Cell as Diagnostic Biomarker for Early Detection And Treatment of Maxilarian Cancer: Review Article - Thongiratama, Gregorius William; Dhananjaya, Gede Arya Diva; Mulya, Happy Kusuma; Ruma, I Made Winarsa (http://dharmais.co.id/, 2024)
Background: Squamous cell carcinoma (SCC) has a higher chance of occurance and progression in maxillary sinus cancer than other paranasal sinus cancers (80%). Matrix metalloproteinase-7 (MMP-7) is a protease specified in collagen type IV degradation and Heparin Binding Epidermal Growth Factor activation, which causes an increase in squamous cell carcinoma proliferation and metastasis Methods: This review aims to identify the potential role of MMP-7 as a target for prevention and therapeutic modality to manage SCC sinus maxillary cancer. We did literature searching in several databases to elucidate the importance of the MMP-7 pathway in SCC sinus maxillary cancer progression. Results: : Increasing expression and activity of MMP-7 are associated with maxillary sinus cancer progression. Squamous cells, the most impacted in maxillary sinus cancer, sustain dysplasia due to heparin-binding epidermal growth factor (HB-EGF) activation into EGF by MMP-7 and Cluster of Differentiation 44 (CD44) binding complexes that trigger high proliferation and mitogenic activity. The therapeutic function of MMP-7 occurs by affecting the protein 53 (p53) in cancer cell apoptosis initiation by specific interaction with CD44. Conclusion: MMP-7 could be an alternative therapeutic target and potential treatment option for maxillary sinus cancer. Furthermore, more trials should be done to test the relevancy of MMP-7 uses as an SCC sinus maxillary cancer modality